A COMPARATIVE STUDY OF AUDIO AND VIDEO LISTENING PRACTICES AT THE TENTH GRADE STUDENTS OF A SENIOR HIGH SCHOOL IN PURWAKARTA - Hidayatullah, Alfikri; Sakina, Rahma; Yunita, Sri (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
This study aimed to finding comparative of the audio and video media that are used in the school to know the significant difference between students’ listening comprehension by using video and audio on learning process. The research used a quantitative method approach which use comparative design. Population of this study research was 64 students and the samples were 30 students. In collecting the data, the researcher used listening test. Based on the finding of the research, the conclusions can be explained that the first and the second test has different topic and both test has different result of hypothesis testing, which in the first test that discussed the topic about some dialogues and conversations, the t-test value was 13.00 and t-table for n = 58 in level of significant α = 0.05 was 2.00. Because of t-test > t-table (13.15 > 2.00), it means that there is a significant difference between the students listening comprehension by using video and audio. Meanwhile in the second test which discussed the topic from cut movie, the t-test value was -10.15 and t-table was 2.00. Because of t-test < t-table (-10.15 < 2.00), it means that there is not a significant difference between the students listening comprehension by using video and audio. The result of this research shows that video is a better media than audio to be applied on students‟ listening comprehension, therefore the implementation of this research expects the teachers/ lecturers to use video as learning media in teaching listening especially in listening comprehension.